Korelasi Positive Parenting dengan Kompetensi Sosial Mahasiswa Rantau - Mary Philia Elisabeth; Srisiuni Sugoto; Vita Anggraini (Universitas Muhammadiyah Jember, 2021)
This study aims to determine the positive relationship between parenting and social competence among overseas students. This study uses a survey method with an attitude scale to collect data online using google form. Sampling was carried out using the incidental sampling technique and it was found that there were 170 overseas students from several regions in Indonesia with an age range of 18-25 years, currently still in overseas areas, living in overseas areas for at least 1 year, and still having complete parents. Data obtained using the Social Skills Rating System to measure social competence and the Multidimensional Assessment of Parenting Scale to measure positive parenting. Data analysis was performed using SPSS for Windows version 25. The results of hypothesis testing showed the value of r = 0.297 with p = 0.001 (p 0.05) so that there was a positive correlation between positive parenting and the social competence of overseas students. The results showed that most of the participants had social competence and parents who applied positive parenting in the high and very high categories.